Pretreatment Vitamin D deficiency is associated with impaired progression-free and overall survival in hodgkin lymphoma - Borchmann, Sven; Cirillo, Melita; Goergen, Helen; Meder, Lydia; Sasse, Stephanie; Kreissl, Stefanie; Broeckelmann, Paul Jan; Von Tresckow, Bastian; Fuchs, Michael; Ullrich, Roland Tillmann; Engert, Andreas (Journal of Clinical Oncology, 2019)
PURPOSE Vitamin D deficiency is described as a modifiable risk factor for the incidence of and mortality in many common cancers; however, data in Hodgkin lymphoma (HL) are lacking. PATIENTS AND METHODS We thus performed a study measuring pretreatment Vitamin D levels in prospectively treated patients with HL and correlated this with clinical outcomes. A total of 351 patients from the German Hodgkin Study Group clinical trials (HD7, HD8, and HD9) were included. RESULTS Fifty percent of patients were Vitamin D deficient (, 30 nmol/L) before planned chemotherapy. Pretreatment Vitamin D deficiency was more common in relapsed/refractory patients than matched relapse-free controls (median baseline Vitamin D, 21.4 nmol/L v 35.5 nmol/L; proportion with Vitamin D deficiency, 68% v 41%; P <.001). Vitamin D-deficient patients had impaired progression-free survival (10-year difference, 17.6%; 95% CI, 6.9% to 28.4%; hazard ratio, 2.13; 95% CI, 1.84 to 2.48; P<001) and overall survival (10-year difference, 11.1%; 95% CI, 2.1% to 20.2%; hazard ratio, 1.82; 95% CI, 1.53 to 2.15; P <.001), consistent across trials and treatment groups. We demonstrated that Vitamin D status is an independent predictor of outcome and hypothesized that Vitamin D status might be important for the chemosensitivity of HL. We subsequently performed experiments supplementing physiologic doses of Vitamin D (calcitriol) to cultured HL cell lines and demonstrated increased antiproliferative effects in combination with chemotherapy. In an HLxenograft animal model, we showed that supplemental Vitamin D (dietary supplement, cholecalciferol) improves the chemosensitivity of tumors by reducing the rate of tumor growth compared with Vitamin D or chemotherapy alone. CONCLUSION On the basis of our clinical and preclinical findings, we encourage that Vitamin D screening and replacement be incorporated into future randomized clinical trials to properly clarify the role of Vitamin D replacement therapy in HL.
CRIS-Team Scopus Importer:2023-03-21